Development of Ethno-vlog Media and Virtual Reality (VR) Teh Oyol Ecology and Biodiversity Materials to Equip Students Science Process Skills - Luky Hidayat; Sudarmin; Hendra Febriyanto; Norma Eralia; Sunardi (ISEJ : Indonesian Science Education Journal, 2024)
Education in the 21st century requires innovative approaches that integrate technology and local wisdom to strengthen students’ science process skills (SPS). This study aims to develop, validate, and evaluate the effectiveness of ethno-vlog and virtual reality (VR) media based on the cultural context of Oyol tea in enhancing junior high school students’ SPS on ecology and biodiversity topics. Employing a research and development design with the 4D model (Define, Design, Develop, Disseminate), this study involved small-scale (n = 15) and large-scale (n = 32) trials with grade VII and VIII students at a junior high school in Indonesia. Data were collected through expert validation, student response questionnaires, observation sheets, and pre-post assessments of SPS. The results indicated that both media met the “very feasible” criteria from expert validators (average ≥ 87.5%) and received highly positive responses from students. Statistical analysis using N-gain (0.76, high category) and the Mann–Whitney test (p < 0.05) confirmed a significant improvement in students’ SPS, particularly in observation, prediction, inference, classification, measurement, and communication skills. These findings demonstrate that the integration of ethnoscience-based vlog and VR provides a meaningful, interactive, and culturally relevant learning experience. The study contributes to digital pedagogy by bridging local knowledge and advanced technologies, offering a scalable model for science education in developing countries. Future research may extend this approach to other cultural contexts and subject areas to strengthen broader applicability.